The Optimalization of Online Based Qur’an Teacher Training: SWOT Analysis for Improving the Quality of Education - Ningsih, Indah Wahyu; Heriyansyah, Heriyansyah; Kohar, Ade (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
The increasing demand for qualified Qur’an teachers in the digital era requires innovative training models that combine pedagogical quality with technological accessibility. The Tilawati Method, a widely used system for Qur’anic recitation instruction in Indonesia, has been adapted into an online format to meet this need. This study aims to optimize the implementation of online-based Qur’an Teacher Training using the Tilawati Method with a SWOT analysis approach to improve the quality of education. This study uses a qualitative method with data collection through interviews, observations, and documentation studies that are analyzed using a SWOT matrix. The results of the analysis show strengths such as time flexibility, cost efficiency, and detailed program structure; weaknesses such as dependence on internet connections and limitations of practice sessions; opportunities in equitable access to Qur’anic education; as well as threats in the form of infrastructure constraints and miscommunication between institutions. The proposed strategy includes technology optimization, improving post-training assistance services, and strengthening cooperation between central institutions and branches. This research is expected to be the basis for the development of Qur’an-based education policies based on the Tilawati Method that is continuous improvement.